GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA GURU DAN STAFF DI MI SEKOLAH CINTA ILMU - Cepi Budianto; Toni Yoga Ramadhan (Institut Ummul Quro Al-Islami Bogor, 2023)
Leadership in education is the key to implementing effective education. The selection of the right leadership style by the school principal will be able to lead the school towards improving quality and service. This research aims to describe and analyze the leadership style of school principals in an effort to improve the performance of teachers and education staff at MI Sekolah Cinta Ilmu and to explore the factors that influence the leadership style of school principals at MI Sekolah Cinta Ilmu. This research uses a descriptive qualitative approach with a case study research design. The data collection techniques used were non-participant open observation, semi-structured interviews and documentation studies. Data validity techniques use credibility, transferability, dependability and confirmability. The results of the research can be explained as follows: (1) the principal's leadership style is concluded from eight aspects that have been determined by the researcher, namely: (a) the daily behavior of the principal shows an attitude of attention, openness, cheerfulness, firmness, wisdom, discipline and commitment and has emotions. which is stable; (b) delegation of tasks is carried out fairly and direction is given; (c) decision making is carried out jointly/consensusally; (d) supervision is carried out by directly monitoring progress; (e) school development includes development of school facilities and infrastructure, extracurricular activities, learning and teachers and educational staff; (f) open and two-way communication with clear and easy to understand language; (g) motivation by providing encouragement/encouragement and fulfilling the needs of all school personnel and (h) rewards in the form of praise and thanks. In leading the school principal uses a group leadership style. So it can be understood that in an effort to improve the performance of teachers and education staff, school principals empower teachers and education staff, develop the competence of teachers and education staff, provide motivation and rewards; (2) factors that influence the group leadership style are: (a) the leader himself has personality, past experience, and high expectations for all school personnel to develop the school; (b) characteristics of superiors who prioritize the process of carrying out tasks; (c) subordinate characteristics that demonstrate enthusiasm and willingness to change; (d) task requirements by providing guidance regarding task clarity; (e) organizational climate and policies can help improve the quality of human resources in the school environment